Os trajes nobres femininos da corte carioca nas aquarelas de Jean-Baptiste Debret (1817-1827) - Lopes, Charles Roberto Ross (2021)
This thesis investigates the noble feminine clothing from the Rio de Janeiro court, between 1817 and 1827, based on Jean-Baptiste Debret´s watercolors. Due to the great dimension of this artist's work, 12 finished watercolors were selected, belonging to Castro Maya Collection, in which it is possible to explore the details of the costumes. The academic basis embranced in the argumentative construction of the text is based on the premise that the social fabric can be understood, among other elements, from clothing and fashion. Thereby, in the perspective of a Social History of clothing, it analyzes how the Portuguese dress influenced the elaboration of the clothing used by the ladies from local elites, which makes it possible to understand how the values of the European civilization are disseminated and incorporated by the society of Rio de Janeiro, starting from the creation of a new clothing aesthetic. The research writing begins with a chapter dedicated to the presentation of tailors, seamstresses and dressmakers who settle down at the court. Therefore, it uses advertisements from Gazeta do Rio de Janeiro, considering that they reveal important aspects of the new fashion circuit. In this contextualization movement, it still uses some reports from travelers who passed through the city. The aesthetic references of European fashion, in the transition period from the 18th to the 19th century, are explored in Chapter 2, which addresses the transformations that occurred in women's clothing after the French Revolution, as well as the development of Portuguese fashion in this context, based on analysis of some pieces from the Museu Nacional do Traje de Lisboa. Finally, the Debret´s watercolors are analyzed, taken as the main historical source to verify that elements of Lusitanian fashion have been preserved and adapted to the local context. When discussing the relations established between these images, the sociability and the ways of dressing of that time, the various pieces that make up the noble feminine dress are verified.